THE EMERGENCE OF THE FILM FESTIVAL INDUSTRY IN THE REPUBLICS OF UZBEKISTAN AND TURKMENISTAN DURING THE YEARS OF INDEPENDENCE - Shakhzod, Oromov (PT. Antis International Publisher, 2025)
Objective: This study investigates the development of the film festival industry in Uzbekistan and Turkmenistan, with a focus on its role in cultural diplomacy, regional integration, and the promotion of national cinema in the post-Soviet context. Method: A historical and qualitative approach was employed, involving the analysis of archival sources, policy documents, and contemporary case studies of film festivals in both countries. Results: The research reveals that film festivals in Central Asia have evolved from Soviet-era ideological instruments into vital platforms for cultural expression, artistic innovation, and regional collaboration. Uzbekistan has emerged as a regional leader in hosting international film events and reviving cultural diplomacy through cinema. However, challenges remain, including inconsistent funding, low organizational standards, and the persistence of outdated thematic content. Novelty: This study provides one of the first comparative assessments of film festivals in Uzbekistan and Turkmenistan, offering a nuanced understanding of their dual historical and contemporary roles. It highlights the potential of film festivals to contribute to national identity formation and regional soft power while calling for institutional reforms and creative diversification to enhance global visibility and impact.